Temporal structure of firm growth and the impact of R&D - Antje Schimke; Thomas Brenner (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2011)
This paper examines the time structure of the effects of R&D activities on firm growth. The main questions are whether R&D activities come together with firms' growth in the subsequent periods and how this relationship depends on other characteristics of the firms, such as size and industry. In addition, we study the relationship between R&D effects and the autocorrelation dynamics of firm growth. We use firm level data of 1000 European companies with details on R&D investments in 2003 to 2006. A regression approach is applied with a linear model taking into account R&D activities at points in time and autocorrelation dynamics of firm growth. We find that R&D has, on average, a positive effect on firm growth, but the effect and its temporal structure strongly depends on firm size and industry.
urn:nbn:de:swb:90-237006
Keywords: 330; Firm growth; R&D activities; firm size; industry; autocorrelation; time gap; temporal structure